Corporate reputation: Perspectives of employees in Celcom (M) Berhad / Siti Zulaikha Ramli - Ramli, Siti Zulaikha (Faculty of Business and Management, 2006)
The subject of corporate reputation has attracted interest among marketing academies and practitioners for the last four decades. Recently, the increasing importance that managers place on the value of sustaining a favorable corporate reputation has been reflected through a whole industry devoted to profiling corporate reputations and the Marketing Science Institute's call for a research on corporate image, corporate reputation and the value of being seen as a "good company". Although the term reputation is clearly defined as the estimation in which one is held; character in public opinion; the character to attribute to a person, thing or action; over the years authors in this area have adopted different, sometimes even contradictory definitions for the term corporate reputation.